Knowledge Management Process as a Predictor on Organizational Performance in Dubai Government Departments (European Journal of Marketing and Economics, 2019)
In recent years, the concept of Knowledge Management has expanded widely in government and private sectors. The last five years have witnessed intensive discussions on Knowledge Management and its importance. The aim of this study is to examine the relationship between Knowledge Management and its aspects and its impact on the performance of the governmental institutions in the Emirate of Dubai from the point of view of the managers of these institutions. This study attempts to use the analytical descriptive method to address the subject of the research. In this light, the analytical framework drawn integrates these approaches and can be applied in empirical studies. The study uses the questionnaire in data collection, which is valid and reliable according to the Cronbach’s Alpha value. A Multiple linear regression analysis has been used to predict the OP based on KG, KSR and KST. The findings showed that KG, KSR and KST were the key predictors of OP as these explained 49.6% of the total variance in Model.
Keywords: knowledge, management, organization, performance